A New Approach for Fabricating Collagen/ECM‐Based Bioinks Using Preosteoblasts and Human Adipose Stem Cells. Issue 9 (15th April 2015) - Lee, Hyeong Jin; Kim, Yong Bok; Ahn, Seung Hyun; Lee, Ji‐Seon; Jang, Chul Ho; Yoon, Hyeon; Chun, Wook; Kim, Geun Hyung
<x xml:space="preserve">Abstract</x> Cell‐printing methods have been used widely in tissue regeneration because they enable fabricating biomimetic 3D structures laden with various cells. To achieve a cell‐matrix block, various natural hydrogels that are nontoxic, biocompatible, and printable have been combined to obtain "bioinks." Unfortunately, most bioinks, including those with alginates, show low cell‐activating properties. Here, a strategy for obtaining highly bioactive ink, which consisted of collagen/extracellular matrix (ECM) and alginate, for printing 3D porous cell blocks is developed. An in vitro assessment of the 3D porous structures laden with preosteoblasts and human adipose stem cells (hASCs) demonstrates that the cells in the bioinks are viable. Osteogenic activities with the designed bioinks show much higher levels than with the "conventional" alginate‐based bioink. Furthermore, the hepatogenic differentiation ability of hASCs with the bioink is evaluated using the liver‐specific genes, albumin, and TDO2, under hepatogenic differentiation conditions. The genes are activated within the 3D cell block fabricated using the new bioink. These results demonstrate that the 3D cell‐laden structure fabricated using collagen/ECM‐based bioinks can provide a novel platform for various tissue engineering applications.